2007
DOI: 10.3748/wjg.v13.i41.5506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of large dose of dexamethasone on inflammatory mediators and pancreatic cell apoptosis of rats with severe acute pancreatitis

Abstract: AIM:To investigate the influence of high dose of dexamethasone on inflammatory mediators and apoptosis of rats with severe acute pancreatitis (SAP).METHODS: SAP rats were randomly assigned to the model group and treatment group while the normal rats were assigned to the sham operation group. The mortality, ascite volumes, ascites/body weight ratio and pancreas pathological changes of all rats were observed at 3, 6 and 12 h after operation. Their contents of amylase and endotoxin in plasma and contents of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…A previous study demonstrated that pancreatic cell apoptosis occurs during acute pancreatitis (34). Animal experiments also suggested that dexamethasone induces pancreatic cell apoptosis, stabilizes the internal environment and attenuates inflammation in pancreatic tissues (33,35). In the present study, dexamethasone enhanced the phagocytotic capacity of pMФs, maintained the internal environment and increased MФ ICAM-3 expression.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…A previous study demonstrated that pancreatic cell apoptosis occurs during acute pancreatitis (34). Animal experiments also suggested that dexamethasone induces pancreatic cell apoptosis, stabilizes the internal environment and attenuates inflammation in pancreatic tissues (33,35). In the present study, dexamethasone enhanced the phagocytotic capacity of pMФs, maintained the internal environment and increased MФ ICAM-3 expression.…”
Section: Discussionsupporting
confidence: 51%
“…The effects of glucocorticoids on inflammation via receptor mediation may trigger anti-inflammatory processes. Glucocorticoids inhibit inflammatory exudation, leukocytic infiltration and inflammatory mediator production and release, improve the microcirculation, alleviate endotoxemia and induce apoptosis of pancreatic acinar cells, thereby reducing the degree of pancreatic necrosis in SAP (32,33). A previous study demonstrated that pancreatic cell apoptosis occurs during acute pancreatitis (34).…”
Section: Discussionmentioning
confidence: 99%
“…After inserting a segmental epidural catheter into the duodenum cavity via the hole, it was inserted into the biliary-pancreatic duct, in the direction of the papilla, in a retrograde position. This was followed by retrograde transfusion of 3.5% sodium taurocholate 0.1 mL/100 g by microinjection pump at the speed of 0.2 mL/min, and then the hole in the duodenum lateral wall was sutured [2][3][4][5][6] .…”
Section: Animal Grouping and Rat Sap Model Preparationmentioning
confidence: 99%
“…Salvia miltiorrhiza ('Danshen' in Chinese) injection and dexamethasone injection are representative traditional Chinese and Western medicines, respectively, most frequently used for the treatment of SAP patients. Salvia miltiorrhiza exerts therapeutic effects on SAP mainly by improving microcirculation, while dexamethasone acts mainly through suppressing inflammatory mediators (Zhang et al, 2007d;2007e). Salvia miltiorrhiza is a commonly used Chinese herb for promoting blood flow and removing blood stasis.…”
mentioning
confidence: 99%